CD4 T Follicular Helper and Regulatory Cell Dynamics and Function in HIV Infection - Miles, Brodie; Miller, Shannon M.; Connick, Elizabeth (Frontiers in Immunology, 2016)
T follicular helper cells (TFH) are a specialized subset of CD4 T cells that reside in B cell follicles and promote B cell maturation into plasma cells and long-lived memory B cells. During chronic infection prior to the development of AIDS, HIV-1 (HIV) replication is largely concentrated in TFH. Paradoxically, TFH numbers are increased in early and midstages of disease, thereby promoting HIV replication and disease progression. Despite increased TFH numbers, numerous defects in humoral immunity are detected in HIV-infected individuals, including dysregulation of B cell maturation, impaired somatic hypermutation, and low quality of antibody production despite hypergammaglobulinemia. Clinically, these defects are manifested by increased vulnerability to bacterial infections and impaired vaccine responses, neither of which is fully reversed by antiretroviral therapy (ART). Deficits in TFH function, including reduced HIV-specific IL-21 production and low levels of co-stimulatory receptor expression, have been linked to these immune impairments. Impairments in TFH likely contribute as well to the ability of HIV to persist and evade humoral immunity, particularly the inability to develop broadly neutralizing antibodies. In addition to direct infection of TFH, other mechanisms that have been linked to TFH deficits in HIV infection include upregulation of PD-L1 on germinal center B cells and augmented follicular regulatory T cell responses. Challenges to development of strategies to enhance TFH function in HIV infection include lack of an established phenotype for memory TFH as well as limited understanding of the relationship between peripheral TFH and lymphoid tissue TFH. Interventions to augment TFH function in HIV-infected individuals could enhance immune reconstitution during ART and potentially augment cure strategies.